Imaging the posterior mediastinum: a multimodality approach - Mariaelena Occhipinti; Benedikt H. Heidinger; Elisa Franquet; Ronald L Eisenberg; Alexander A. Bankier (Diagnostic and Interventional Radiology, 2015)

(untitled)
The posterior mediastinum contains several structures that can produce a wide variety of pathologic conditions. Descending thoracic aorta, esophagus, azygos and hemiazygos veins, thoracic duct, lymph nodes, adipose tissue, and nerves are all located in this anatomical region and can produce diverse abnormalities. Although chest radiography may detect many of these pathologic conditions, computed tomography and magnetic resonance are the imaging modalities of choice for further defining the relationship of posterior mediastinal lesions to neighboring structures and showing specific imaging features that narrow the differential diagnosis. This review emphasizes modality-related answers to morphologic questions, which provide precise diagnostic information.